(3TQM ZQjH GdSjQI GdfHhjIs - (3CHh PQ eUYH Hf eMeO (B( (3CHi HcQ (B) (3Hf eSYhO GdNTfi GdLjGfis; (3eMeO Hf GSMGb Hf jSGQ GdeWdHj HGdhdGA, GdeOfj,J (B151 (3g` s ((3eGdbI s)
(3ChdgG (B:s
(3bGd GdTjN Gdabjg GdNTfi (B( (3QVi Gddg Yfg (B) : (3GdMeO ddg HGYK GdQSd hfGgL GdSHd , GdPi gOGfG ddESdGe s
(3BNQgG (B:s
(3GdCdjI (B: (3Gdjejf hGdMda hGdeHGPd (B: (3LeY eHPd , hgh GdKhH GdPi jJHPd ajg hGdUGOi(B: (3GdYGWT GfJgi eG CedjfG Ydi cJGH SjQI QShd Gddg (B( (3Udi Gddg Ydjg hSde (B) (3hCOH LdjfGg hhTMfGg s
(3GdfSNI ebGHdI fSNI SeYJ Ydi GdeUfa SfI (B603(3g`s
(3hYdjgG eYGQVI CNQi JGQjNgG (B641(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GddZIs